2009
DOI: 10.1002/apj.267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of circulating fluidized bed combustion (CFBC) fly ashes as filler on the performances of asphalt

Abstract: This work investigated the potential of utilizing circulating fluidized bed combustion (CFBC) fly ashes (CFAs) as alternative filler, substituting mineral powders (MPs) that are widely used in asphalt concrete. Physicochemical characteristics of the CFAs and MPs, as well as effects of different mix designs of CFAs and asphalt on asphalt performances were examined, including moisture susceptibility, viscosity, ductility, softening point, penetration, and antiaging performances. The results of the study show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…FBCFA has been found to be more suitable for asphalt concrete than virgin mineral powders. Li et al [170] investigated the potential of utilizing FBCFA as an alternative filler, substituting mineral powders that are widely used in asphalt concrete. Their results showed that generally FBCFAs have a greater effect on improving the performances of asphalt and that the specific surface area, free CaO, morphology, and mineralogical phases of the FBCFAs are more favorable than those of the mineral powders, respectively, while the alkaline values, hydrophilic coefficients, particle size distributions, and water contents of the two fillers are similar.…”
Section: Road Constructionmentioning
confidence: 99%
“…FBCFA has been found to be more suitable for asphalt concrete than virgin mineral powders. Li et al [170] investigated the potential of utilizing FBCFA as an alternative filler, substituting mineral powders that are widely used in asphalt concrete. Their results showed that generally FBCFAs have a greater effect on improving the performances of asphalt and that the specific surface area, free CaO, morphology, and mineralogical phases of the FBCFAs are more favorable than those of the mineral powders, respectively, while the alkaline values, hydrophilic coefficients, particle size distributions, and water contents of the two fillers are similar.…”
Section: Road Constructionmentioning
confidence: 99%
“…Normally, CFAs conform to neither North American standards nor European ones for components or additives in concretes (Blondin and Anthony, 1995). The unique thermal history, featuring low combustion temperatures of 800-950°C, makes CFAs differ greatly in physical and chemical characteristics from PFAs, whose typical firing temperatures are 1200-1400°C (Anthony et al, 2002;Li et al, 2009). Eventually, the low combustion temperature may lead to a low pozzolanic activity (Iribarne et al, 2001), which is partially responsible for the poor feasibility of utilizing CFAs in cement industry.…”
Section: Introductionmentioning
confidence: 99%